2014
DOI: 10.1371/journal.pone.0108534
|View full text |Cite
|
Sign up to set email alerts
|

Human Leptospirosis: Seroreactivity and Genetic Susceptibility in the Population of São Miguel Island (Azores, Portugal)

Abstract: BackgroundLeptospirosis is a worldwide zoonotic and recognized neglected infectious disease. It has been observed that only a proportion of individuals exposed to pathogenic species of Leptospira become infected and develop clinically evident disease. Moreover, little information is available in subsequent reinfections. In the present study, we determine if a first infection with leptospirosis protects against subsequent reinfection, and investigate which of the host genetic factors are involved in the suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 31 publications
3
36
0
2
Order By: Relevance
“…The data showed that males and farmers were the most affected by this pathogen. These results are in accordance with the study developed by Vieira et al [5] and Esteves et al [6], where a significant link to professional activities and/or contact with rodents and domestic animals (natural reservoirs for leptospires) was observed.…”
Section: Molecular Diagnosis Of Leptospirosissupporting
confidence: 93%
See 1 more Smart Citation
“…The data showed that males and farmers were the most affected by this pathogen. These results are in accordance with the study developed by Vieira et al [5] and Esteves et al [6], where a significant link to professional activities and/or contact with rodents and domestic animals (natural reservoirs for leptospires) was observed.…”
Section: Molecular Diagnosis Of Leptospirosissupporting
confidence: 93%
“…These spirochetes are responsible for severe human disease leading to a systemic infection, characterized by clinical manifestations that vary greatly from flu-like symptoms to multiple organ failure and death [6]. Leptospirosis is known for its endemicity, and is considered a public health problem due to its high annual incidence rate in semi-tropical climates, such as the Azores Islands (Portugal) [5,6]. Transmission of leptospirosis can occur through direct contact with an infected animal or its urine, placental fluids, or milk.…”
Section: Molecular Diagnosis Of Leptospirosismentioning
confidence: 99%
“…( C ) Corresponding to each of the polymorphisms indicated in (A) are reports of its association with disease susceptibility or outcome; listed below each polymorphism is whether this is an infectious disease (ID), cancer (CA), pediatric asthma (PA) or dermatological disease (DD). The literature references supporting these assignments are described in the article text and reproduced here: rs393548 (116), rs436857 (116), rs2305742 (146), rs429774 (135, 158), rs11575934 (130, 145), rs375947 (130, 144, 158), rs401502 (130, 137), rs372889 (139, 140), rs383483 (135). Given that rs11575934, rs375947, and rs401502 are frequently linked, they are often referred to in the literature as the “RTR haplotype” (129) ( D ) Depicted are the thirteen alternative splice variants expressed in human PBMCs and lung tissue.…”
Section: Figurementioning
confidence: 99%
“…liver dysfunction, myocarditis). Among individuals living on the Azores archipelago (Portugal), Esteves et al (137) reported that the rs401502 allele conferred susceptibility to pathogenic leptospira. Finally, unlike TB, malaria or leptospirosis, measles is of viral origin (a paramyxovirus of the genus Morbillivirus) and is vaccine-preventable.…”
Section: Introductionmentioning
confidence: 99%
“…However, our patients represent primarily individuals of mixed Caucasian and African descent and it will be important to identify whether the pathways we identified are generalizable to global populations, given that several studies have shown association of specific alleles with increased susceptibility to leptospirosis [15, 16, 58, 59]. Further, it will be important to compare our findings on whole blood transcriptional profile with samples from the lungs in patients that develop LPHS.…”
Section: Discussionmentioning
confidence: 99%